Pengaruh Sikap Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Kinanty Patopang - ., A. Dirwan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
The purpose of this study was to determine the influence of work attitude and motivation on employees pefonnance at PT Kinanty Patopang. The subject of this research were 50 employees. By using 5 Likert Scale. The frame work of this research was based on that work attitude (X1) and work motivation (X2) had influence of employees performance (Y). The work attitude was measured bay 30 items question, work motivation was measured bay 31 items question, and employees performance was measured with 39 items question/statement. Data analysis used in this research was a multiple regression to analyzed data. Obtained data then were examined with SPSS17.0 version. From the research it can concluded that: (I) there was influence of work attitude toward employees performance; (2) there was influence of work motivation toward employees performance, (3) there was influence of work attitude and work motivation simultaneously toward employees performance of PT. Kinanty Patopang.